2011
DOI: 10.3892/ijmm.2011.786
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol stimulates osteoblastogenesis by suppressing NF-κB activation

Abstract: Abstract. Magnolia officinalis, a component of Asian herbal teas, has long been employed in traditional Japanese and Chinese medicine to treat numerous maladies. Honokiol, a biphenolic compound, is now considered to be one of the major active ingredients of Magnolia extract, and is under intense investigation for its anti-angiogenic, anti-inflammatory, antitumor and neuroprotective properties. Biochemically, honokiol has been recognized to modulate the nuclear factor κ B (NF-κB) signal transduction pathway sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…TNFα further antagonizes BMP signaling by upregulating Smad ubiquitination regulatory factor 1 (Smurf1), promoting proteasomal degradation of bone morphogenetic signaling proteins [42]. Consistent with this data we have reported that multiple suppressors of NF-κB activation including the carotenoid beta-cryptoxanthin [43], the biphenol honokiol [19], vitamin K 2 [9], quercetin [20], zinc [24] and a pharmacological NF-κB inhibitor based on the NEMO binding domain [1] are all capable of rescuing the inhibitory effect of TNFα on BMP2 and/or TGFβ-induced Smad activation.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…TNFα further antagonizes BMP signaling by upregulating Smad ubiquitination regulatory factor 1 (Smurf1), promoting proteasomal degradation of bone morphogenetic signaling proteins [42]. Consistent with this data we have reported that multiple suppressors of NF-κB activation including the carotenoid beta-cryptoxanthin [43], the biphenol honokiol [19], vitamin K 2 [9], quercetin [20], zinc [24] and a pharmacological NF-κB inhibitor based on the NEMO binding domain [1] are all capable of rescuing the inhibitory effect of TNFα on BMP2 and/or TGFβ-induced Smad activation.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, we have recently reported that several natural compounds, long believed to possess anabolic and/or anti-catabolic properties, may protect bone by antagonizing NF-κB activation. Among these agents are vitamin K 2 [9], 17beta-estradiol [17], the carotene, p-hydroxycinnamic acid, the xanthophyll, beta-cryptoxanthin [18], honokiol, a component of Asian herbal teas used extensively in traditional Japanese and Chinese medicine [19], and the plant-derived flavonoid quercetin [20]. …”
Section: Introductionmentioning
confidence: 99%
“…It was reported that HNK induces osteoblast differentiation in vitro because of its capacity to inhibit basal and TNF-α-induced NF-κB activation and to reduce the suppressive action of TNF-α on BMP-2-induced Smad activation [20,21] . Based on this, we examined whether Smad and NF-κB signaling were linked with c-FLIP after NSCLC cells were exposed to HNK.…”
Section: C-flip Regulates the Expression Of Iκbα But Not P-smad2/3mentioning
confidence: 99%
“…We have shown that vitamin K2 [114], Honokiol [115], Zinc [116], and the carotenoid p -hydroxycinnamic [117, 118] are all capable of modulating NF- κ B activation in osteoblast and osteoclast precursors in vitro by antagonizing RANKL- and TNF α -induced NF- κ B activation in osteoblasts and osteoclasts, respectively.…”
Section: Nf-κb and Bone Formationmentioning
confidence: 99%